Pengelolaan Limbah Cair PT. Pelindo III Cabang Tanjung Emas di Semarang - Muhammad. Reza Kusman; Hartati Kapita; Elfira Resti Mulya (Peneliti.net, 2020)
PT. Pelabuhan Indonesia III (Persero) or better known as Pelindo III is one of the State Owned Enterprises (BUMN) which is engaged in port terminal operator services. As a port terminal operator, Pelindo III manages 43 ports with 16 branch offices spread across seven provinces in Indonesia. The purpose of writing this research is to determine the management of liquid waste at PT. Pelindo III. Tanjung Emas Branch, the research method used was data collection by means of interviews and field observations by means of descriptive analysis. In this way the handling and management of waste should pay attention to Regulation of the Minister of Environment Number 05 of 2009 concerning Waste Management at Ports and Law No. 32 of 2009 concerning Protection and Management of the Environment. The results of this study that the source of waste contained in PT Pelindo III came from loading and unloading activities. The main waste is oil spills, and also office activities